2020
DOI: 10.1109/trpms.2019.2936667
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking of Human Body Electrical Characteristic for Easier Translation of Plasma Biomedical Studies to Clinical Applications

Abstract: Non-thermal plasma (NTP) medical applications are now well established but the translation from in vitro plasma effects to in vivo effects remains far from being intuitive. Among various possible reasons, the translation may be disturbed by a loose control over the electrical characteristics of the different targets (e.g. cell culture dish, animal models) met during the development process, a parameter generally neglected and often unmentioned in papers. The aim of this study is to raise consciousness on how t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 24 publications
(28 reference statements)
1
51
0
Order By: Relevance
“…The range of intensities of the µsPEF that was used in our study has already been demonstrated as non-cytotoxic [33,34]. The work reported in the results section was performed with a setup optimised, as described in the results section and in [31] (NTP setup 2), after establishing the proof of concept (Appendix A) with a new NTP multi-jet setup that was recently developed by our group to homogeneously treat large surfaces (NTP setup 1). The NTP setup 2 produced pPBS with reproducible characteristics due to well-controlled exposure of the PBS + / + and allowed for us to examine possible differences in the pPBS effects on the two different cell lines used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The range of intensities of the µsPEF that was used in our study has already been demonstrated as non-cytotoxic [33,34]. The work reported in the results section was performed with a setup optimised, as described in the results section and in [31] (NTP setup 2), after establishing the proof of concept (Appendix A) with a new NTP multi-jet setup that was recently developed by our group to homogeneously treat large surfaces (NTP setup 1). The NTP setup 2 produced pPBS with reproducible characteristics due to well-controlled exposure of the PBS + / + and allowed for us to examine possible differences in the pPBS effects on the two different cell lines used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The NTP multi-jet used in this study is based on a Plasma Gun (PG) device, which was described previously [31]. Briefly, the PG is a coaxial dielectric barrier discharge (DBD) reactor that consists of a quartz capillary tube flushed with helium and a microsecond-pulses high voltage (µs-pulses HV) generator powers it.…”
Section: Specifications Of the Ntp Multi-jet Setupmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, electrical properties, such as conductivity and potential, play a major role [4,7]. During direct plasma treatment, the target becomes part of the transient electrical circuit, connecting the power supply, the plasma source, the plasma, the target and the return to ground [8,9]. This means that the target's electrical parameters (conductivity, potential, etc.)…”
Section: Introductionmentioning
confidence: 99%